Linking Across Borders: Opportunities and Obstacles for a Joint Regional Greenhouse Gas Initiative-Western Climate Initiative Market - Wilson, Augusta (Columbia Journal of Environmental Law, 2019)
Despite the strong consensus in the scientific community that anthropogenic climate change requires urgent attention, neither the United States nor Canada has implemented a comprehensive national policy to reduce greenhouse gas emissions. Into this void have stepped two regional cap-and-trade programs that regulate greenhouse gas emissions in parts of both countries. One, the Regional Greenhouse Gas Initiative (“RGGI”), is a partnership of nine states in the northeastern and mid-Atlantic U.S. The other, the Western Climate Initiative (the “WCI”), is a partnership between California and the Provinces of Québec and Ontario. Both programs have been operating for several years, demonstrating that cap-and-trade programs can achieve cost- effective emissions reductions. Nonetheless, both markets have faced difficulties at various points, including volatility of allowance prices and the withdrawal of partner jurisdictions. One often-cited mechanism for improving the functioning of cap-and-trade markets is to link them with other markets. In this context, linking is defined as the parties of two or more cap-and- trade programs each agreeing to recognize each other’s allowances for purposes of demonstrating compliance by a regulated source. Political leaders in both RGGI and WCI jurisdictions have repeatedly called for such a linkage between the two programs. In 2006, then-Governors George Pataki of New York and Arnold Schwarzenegger of California announced that they would pursue a partnership between RGGI and the WCI. In 2015, New York Governor Andrew Cuomo issued another public call for the parties to explore a formal linkage between the two markets. Nonetheless, the parties have so far made little progress towards that end. The idea of a RGGI-WCI linkage has taken on a new exigency in recent months, primarily because of the rapid shifts in federal climate change policy following the 2016 U.S. Presidential election. As the federal government rolls back climate regulations, subnational carbon markets such as RGGI and the WCI will need to take on an increasingly central role in mitigating U.S. greenhouse gas emissions, and they may face pressure from environmental advocates to reduce emissions even further than they already have. Successful linkage could help them meet this challenge. While linkage could offer benefits both to RGGI and to the WCI, in order to realize those benefits the two jurisdictions would need to harmonize their cap-and-trade programs in various respects, and the new joint market would need to achieve a certain level of stability. However, the more closely the two programs coordinate with each other to achieve the necessary harmonization, and the more binding—and therefore stable—the linking agreement, the more significant the risk that the agreement would be vulnerable to challenge in U.S. courts under various constitutional doctrines, particularly the dormant foreign affairs power and the dormant foreign commerce clause. This Article examines this tension, evaluates how serious an obstacle it would pose to a potential RGGI-WCI linkage, and seeks to offer solutions that would allow policymakers to develop a linkage that provided the desired benefits, while avoiding constitutional pitfalls. This Article also examines what aspects of the WCI and RGGI programs would be most important to align in order to create a successful joint market that meets both jurisdictions’ policy goals. While the existing linkage of the California and Québec carbon markets under the auspices of the WCI may, to some degree, provide a useful roadmap, a RGGI-WCI linkage would likely pose some new challenges that California and Québec did not face when linking their markets. In particular, while Québec and California developed their carbon markets with integration in mind, RGGI and the WCI developed independently. As a result, there are some significant differences between the two programs that the parties would need to address. This Article begins, in Part II, by reviewing the arguments in favor of linking RGGI and the WCI. Then, in Part III, it draws on interviews with field and academic experts, as well as a review of the relevant literature, to determine the elements of the California and Québec markets that were most important to harmonize for those markets to link effectively. Part IV identifies key differences between RGGI and the WCI, and identifies challenges to linkage that policymakers would need to overcome in order to create a successful joint market. Finally, in Parts V and VI, the Article assesses the constitutional challenges such a linkage may face, and proposes strategies for insulating the linked market from such claims. Ultimately, while opponents of linkage could raise colorable constitutional claims, there are convincing arguments in favor of the constitutionality of such a linking agreement, and it should be possible to design one that avoids potential legal pitfalls and reduces the risk of a constitutional challenge to acceptable levels. Notably, while other scholars have examined the economic theories supporting linkage, as well as the legal issues raised by linkages that cross international borders, this Article appears to be the first to combine a literature review with a series of field interviews. This research offers a new type of pragmatic guide for policymakers considering a linkage.